Risk of visual impairment in patients with neovascular glaucoma and synechial closures of the iridocorneal corner after double transscleral cyclophotocoagulation (Ukrainian Journal of Ophthalmology, 2025)
Purpose: To assess the risk of worsening of visual function at 12 months after diode transscleral cyclophotocoagulation (TSCPC) for neovascular glaucoma (NVG) secondary to diabetic retinopathy (DR) or retinal vein occlusion (RVO) performed at various durations of synechial angle closure.Material and Methods: Two hundred and nine patients (209 eyes) with NVG secondary to DR or RVO were included in the study. In all patients, NVG was accompanied by active neovascularization, and patients varied in the duration of angle closure at the initiation of TSCPC. Median (interquartile (IQR) range) intraocular pressure (IOP) and best-corrected visual acuity (BCVA) at baseline were 36.0 (33; 40) and 0.03 (0.02; 0.06), respectively. Of 209 patients, 38% had prior panretinal photocoagulation (PRP) and antiangiogenic therapy. All patients had a modified diode TSCPC. Treatment success was assessed at 12 months and was defined as an IOP equal to or below 21 mmHg, an improvement in or preservation of preoperative BCVA, and a reduction in or stabilization of preoperative phosphene threshold current (PTC), in the absence of eye pain.Results: At 12 months, 146 (70%) of patients showed no change or an improvement in median BCVA (IQR) to 0.06 (0.03; 0.1) (p < 0.001), and regression of angle and iris neovascularization. Of these, 69 (47%) had prior PRP and antiangiogenic therapy. Cox regression analysis showed that, in patients having no prior PRP or anti-VEGF therapy, the median hazard ratio (95% confidence interval) of a reduction in BCVA at 12 months was 1.1 (0.7; 1.73) for the 6 week duration of angle closure at the initiation of TSCPC, and 4.6 (2.8; 7.7) for the 14 week duration of angle closure at the initiation of TSCPC versus 1.09 (0.6; 1.97) for patients having prior PRP or anti-VEGF therapy.Conclusion: In patients with NVG secondary to DR or RVO and active neovascularization and angle closure, early (≤ 6 weeks after an attack of angle closure) diode TSCPC and prior PRP and anti-VEGF therapy enable a significant reduction in the hazard of worsening of BCVA at 12 months.
Keywords: diabetes mellitus; retinal vein occlusion; neovascular glaucoma; iridocorneal angle; cyclophotocoagulation